Enhancing absorption performance of co2 by amine solution through the spiral wired channel in concentric circular membrane contactors - Ho, C.-D. (MDPI, 2022)
The CO2 absorption rate by using a Monoethanolamide (MEA) solution through the spiral wired channel in concentric circular membrane contactors under both concurrent-flow and countercurrent-flow operations was investigated experimentally and theoretically. The one-dimensional mathematical modeling equation developed for predicting the absorption rate and concentration distributions was solved numerically using the fourth RungeâKutta method under various absorbent flow rate, CO2 feed flow rate and inlet CO2 concentration in the gas feed. An economical viewpoint of the spiral wired module was examined by assessing both absorption flux improvement and power consumption increment. Meanwhile, the correlated average Sherwood number to predict the mass-transfer coefficient of the CO2 absorption mechanisms in a concentric circular membrane contactor with the spiral wired annulus channel is also obtained in a generalized and simplified expression. The theoretical predictions of absorption flux improvement were validated by experimental results in good agreements. The amine solution flowing through the annulus of a concentric circular tube, which was inserted in a tight-fitting spiral wire in a small annular spacing, could enhance the CO2 absorption flux improvement due to reduction of the concentration polarization effect. A larger concentration polarization coefficient (CPC) was achieved in the countercurrent-flow operations than that in concurrent-flow operations for various operations conditions and spiral-wire pitches. The absorption flux improvement for inserting spiral wire in the concentric circular module could provide the maximum relative increment up to 46.45. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.